Using student feedback for successful teaching - Zierer, Klaus (Routledge, 2019)
"Feedback from students to teachers has proven to have a major influence on students' achievement. It is cost-neutral and requires little time. Using Student Feedback for Successful Teaching provides an empirically founded and practice-oriented step-by-step guide to teachers who want to get feedback about their own teaching. The aim of the book is to show why feedback for teachers is important, how teachers can get meaningful feedback and which feedback is helpful and which isn't. This essential teacher guide is closely based on the evidence of the Visible Learning research and includes a foreword by John Hattie" --